Strategi Guru Bimbingan Dan Konseling Dalam Membentuk Karakter Siswa Melalui Berbagai Layanan Bimbingan Dan Konseling Di MTs Nurul Huda Banjar Agung - juwitapradina (MGMP PAI SMP BINTAN, 2026)
This study aims to describe the strategies of Guidance and Counseling teachers in shaping students' character through various guidance and counseling services at MTs Nurul Huda Banjar Agung. Character building is an important aspect of education that plays a role in developing students' positive attitudes, values, and behaviors. This study uses a qualitative approach with a descriptive research type. Data collection techniques were carried out through observation, interviews, and documentation. The research subjects included guidance and counseling teachers, madrasah principals, and students. The results showed that guidance and counseling teachers' strategies in shaping students' character were carried out through personal, social, learning, and career guidance services, as well as supporting activities such as individual counseling, group counseling, and collaboration with homeroom teachers and parents. The character values ​​developed include discipline, responsibility, honesty, politeness, and religiosity. Supporting factors in the implementation of guidance and counseling services include good cooperation between educators and a conducive school environment, while inhibiting factors are limited time and diverse student backgrounds.